Definition of Startup Projects, Main Problems and Prospects of Development (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article is devoted to the study of the definition of startup projects, the main problems and prospects ofdevelopment. Complex analysis of the stages of startup projects and components is carried out. The analysis of institutions that may be investors for start-ups is carried out. Examples of the most famous world and Ukrainian startup projects are given. There was made deep analysis of kraudfanting, as one of the most effective institutions for funding. The present situation of startup development in Ukraine is explored. The actions of the state concerning the given sector, occurring in Ukraine are indicated. The problems and perspectives of development of startup projects are carried out. The necessary measures to improve the conditions for the existence of startup projects in Ukraine are proposed.
Keywords: start-up projects, kraudfanting, business incubator, business accelerator, business angel, project, resources